Resistance Jews and Christians who defied the Nazi terror ; how Jews and Christians fought back against the Nazis - Tec, Nechama 1931-2023 (Oxford Univ. Press, 2013)
A common perception of Jews during World War II is that they were passive and submissive in the face of German oppression. This book questions the validity of this widely held assumption, arguing that rather than making empty claims about Jewish passivity or heroics during the Holocaust, a systematic comparison of Jewish and non-Jewish resistance is needed. Using firsthand accounts and interviews, the book examines the four main settings of the war - ghetto, concentration camp, forest and countryside, and the Aryan world - and describes what life was like for Jews and non-Jews in each.